2015
DOI: 10.7314/apjcp.2014.15.24.10659
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rapamycin on Cell Apoptosis in MCF-7 Human Breast Cancer Cells

Abstract: Background: Rapamycin is an effective anti-angiogenic drug. However, the mode of its action remains unclear. Therefore, in this study, we aimed to elucidate the antitumor mechanism of rapamycin, hypothetically via apoptotic promotion, using MCF-7 breast cancer cells. Materials and Methods: MCF-7 cells were plated at a density of 1510 5 cells/well in 6-well plates. After 24h, cells were treated with a series of concentrations of rapamycin while only adding DMEM medium with PEG for the control regiment and grown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 26 publications
2
20
0
Order By: Relevance
“…Another review obviously demonstrated that rapamycin exhibited inhibitory activity on the MCF-7 cell lines. Direct visualization via inverted microscopy revealed that the MCF-7 cell lines that were cured with ra-pamycin exhibited the properties of apoptosis as well as autophagy, vascularization, and cell shrinkage (22).…”
Section: Discussionmentioning
confidence: 99%
“…Another review obviously demonstrated that rapamycin exhibited inhibitory activity on the MCF-7 cell lines. Direct visualization via inverted microscopy revealed that the MCF-7 cell lines that were cured with ra-pamycin exhibited the properties of apoptosis as well as autophagy, vascularization, and cell shrinkage (22).…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that there was a significant linear correlation between the predominance of the blue hue found in the H‐scan ultrasound images and mean intratumoral apoptotic activity ( R 2 > 0.40, P < .04) in animals administered a single dose of chemotherapy. Given that paclitaxel is a class of chemotherapeutics that inhibits cellular mitosis leading to apoptosis, we theorize that the progressive color map shift observed in the longitudinal H‐scan ultrasound images is, in fact, detection of cancer cell shrinkage in the whole tumor mass as the cells undergo apoptotic death …”
Section: Discussionmentioning
confidence: 99%
“…Characteristic of solid tumors after treatment, this process involves a sequence of intracellular events that systematically dismantle the cell. The first observable change in a cancer cell undergoing apoptosis is physical shrinkage . Drug resistance often prevents cancer cells from undergoing sufficient levels of apoptosis, resulting in cell survival and treatment failure .…”
mentioning
confidence: 99%
“…These preliminary findings strongly suggested the role of GD-triggered autophagy in my study. Moreover, cell death-related research in the past decade has substantially enhanced my current understanding of non-apoptotic programmed cell death events, primarily lysosomal-mediated cell death, necroptosis and autophagy (Amravadi, 2009;Tengku Din et al, 2014) and the complex cross-talk among diverse components of each of these cell death pathways further regulates subsequent cancer progression under stressed/physiologically altered conditions.…”
Section: Discussionmentioning
confidence: 99%